Ocular allergy: update on clinical trials. Issue 5 (October 2019) - Bielory, Leonard; Schoenberg, Dovid
Abstract : Purpose of review: The purpose of this article is to provide an update on the advances made through recent clinical trials regarding the treatment of the signs and symptoms of allergic conjunctivitis and its associated conditions. Recent findings: Recent studies have demonstrated significant advancement in the various forms of immunotherapy treatments. Nutritional interventions such as probiotics have surfaced as a viable complementary treatment option. Novel delivery methods such as contact lenses have been further studied along with a new tacrolimus formulation to improve ocular levels of the drug. Summary: Currently, the primary advances in treatment for allergic conjunctivitis has shifted from new ophthalmic agents to immunotherapy and improvement of drug delivery. This includes the classic subcutaneous and sublingual and the novel epicutaneous and intralymphatic immunotherapy delivery systems as well as an edible rice vaccine. New targets for treatment have spurred research into new antagonist drugs such as (OC000459), a prostaglandin D2 antagonist. The Marinosolv formulation using tacrolimus shows promise and may be considered for other ophthalmic agents in the future. Other nonpharmacological treatments such as stenting and mechanical barrier gel have demonstrated their usefulness in treating ocular symptoms.